Development of a framework and research impact capture tool for nursing, midwifery, allied health professions, healthcare science, pharmacy and psychology (NMAHPPs) - Lisa Newington; Mary Wells; Samina Begum; Andy J. Lavender; Sarah Markham; Oliver Tracy; Caroline M. Alexander (BMC, 2023)
Abstract Background There is an ambitious target to create a UK clinical academic workforce representing 1% of clinicians from nursing, midwifery, the allied health professions, healthcare science, pharmacy and psychology (NMAHPPs). Understanding and recording the impact that clinical academics make across healthcare services is crucial if we are to grow, value and support this highly skilled workforce group. However, it is currently difficult to systematically record, collate and report the impacts associated with NMAHPP research activity. The aims of this project were to i) develop a framework outlining the impacts that were important for key stakeholder groups, and ii) create and pilot a research impact capture tool to record these impacts. Methods The framework was developed from the existing literature. It was refined, remodelled and approved by multidisciplinary stakeholder involvement, including patient and public representatives, healthcare managers and research-active clinicians. The framework was converted into a series of questions to create an electronic research impact capture tool, which was also refined through feedback from these stakeholder groups. The impact capture tool was piloted with research-active clinicians across a large NHS Trust and its associated organisations. Results The impact framework contained eight elements: clinical background, research and service improvement activities, research capacity building, research into practice, patients and service users, research dissemination, economics and research funding, and collaborations. Thirty individuals provided data for the research impact capture tool pilot (55% response rate). Respondents reported a range of positive impacts representing all elements of the framework. Importantly, research-activity appeared to be a key driver for recruitment and retention in the sample population. Conclusions The impact capture tool is a feasible method of recording the breadth of impacts associated with NMAHPP research activity. We encourage other organisations to collaboratively use and refine our impact capture tool, with the aim of standardising reporting, and facilitating discussions about research activity within clinical appraisal. Pooling and comparing data will also allow comparison between organisations, and assessment of change over time or after implementation of interventions aimed at supporting and increasing research activity.